1991
DOI: 10.1177/0261927x91102001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender Inclusive/Exclusive Language in Religious Discourse

Abstract: Religious speech (i.e. preaching) is a prominent language event, yet it has received scant attention in research on language and attitudes. In recent years, many religious institutions have adopted reforms mandating gender-inclusive (non-sexist) language. Only a few studies have examined the effects of gender-inclusive or gender-exclusive language use on listeners' judgments of speakers, and none of these examine religious discourse in particular. In addition, few studies have examined how variables like gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Two studies have, in fact, suggested that awareness of the secondary status of women in U.S. society is associated with attitudes toward sexist language. Greene and Rubin (1991) found that students who were aware that women did not have the same rights in society as men rated the language of a religious sermon more sexist than did other students. Similarly, Harrigan and Lucic (1988) discovered a positive relationship between membership in the National Organization for Women and concern about eliminating sexist language.…”
Section: The Gender Gap In Attitudes Toward Sexist Languagementioning
confidence: 91%
“…Two studies have, in fact, suggested that awareness of the secondary status of women in U.S. society is associated with attitudes toward sexist language. Greene and Rubin (1991) found that students who were aware that women did not have the same rights in society as men rated the language of a religious sermon more sexist than did other students. Similarly, Harrigan and Lucic (1988) discovered a positive relationship between membership in the National Organization for Women and concern about eliminating sexist language.…”
Section: The Gender Gap In Attitudes Toward Sexist Languagementioning
confidence: 91%
“…Indeed, that the multifarious and abundant intersections of politics and religion in the modern world need no introduction, and that highlighting them would be a conspicuous and mundane task, aptly demonstrate the salience of the issue. As an obvious field for scholarly endeavor, the topic of religion is one that has also attracted an intense amount of academic attention, traversing a variety of disciplines, often with interdisciplinary overlap between them, including anthropology (Hann 2007; Saler 2008), history (Morris 2003; Mancini 2007), sociology (Davie 2000, 2006; Coleman, Ivani-Challian and Robinson 2004; Crockett and Voas 2006), law (Greenawalt 1998; Danchin 2008); philosophy (Macdonald 2005; Habermas 2006), psychology (Green and Rubin 1991; Barrett 2000; Boyer 2003; Rossano 2006); economics (Lipford and Tollinson 2003; Fase 2005), and political science (Keddie 1998; Kotler-Berkowitz 2001; Philpott 2007). Within this highly congested scholarly sphere, however, the issue of religious discourse has been something of a neglected area.…”
Section: Religion and Public Discoursementioning
confidence: 99%
“…The findings are mixed. Greene and Rubin (1991) concluded that undergraduates who listened to audiotapes of preachers using gender-exclusive language (i.e., using "he" or "man" when referring to a generic individual) did not judge these ministers more negatively that preachers using gender-inclusive language (i.e., using generic pronouns to describe both genders). However, other researchers have found an inverse association between the use of gender-exclusive language and college students' evaluations of counselors (Johnson & Dowling-Guyer, 1996).…”
Section: Implication For the Study Of School Nicknamesmentioning
confidence: 99%